2016
DOI: 10.1007/s00270-016-1524-x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method of Adrenal Venous Sampling via an Antecubital Approach

Abstract: This study showed that AVS via an antecubital approach was safe and feasible, with a high rate of successful sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 18 publications
1
22
1
Order By: Relevance
“…The left adrenal vein arises from the anterior surface of the gland and joins the left inferior phrenic vein before draining into the left renal vein (63). Some anatomical variations have been described: a common trunk between the right adrenal vein and an accessory hepatic vein in 8% of the cases, while in 10% it is multiple.…”
Section: Patient Preparation and Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The left adrenal vein arises from the anterior surface of the gland and joins the left inferior phrenic vein before draining into the left renal vein (63). Some anatomical variations have been described: a common trunk between the right adrenal vein and an accessory hepatic vein in 8% of the cases, while in 10% it is multiple.…”
Section: Patient Preparation and Techniquementioning
confidence: 99%
“…The jugular vein can be used if necessary. Recently, AVS via an antecubital approach was described in 190 patients as safe and feasible (63).…”
Section: Patient Preparation and Techniquementioning
confidence: 99%
“…Traditionally, AVS has been performed via the femoral vein, with which the success rate of bilateral blood collection is reported to be about 31%‐82%. However, a study reported that the success rate of bilateral blood collection by AVS via the anterior cubital vein is 87.6% 20 . We therefore opted for the upper extremity route (median cubital vein or basilic vein).…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of IHA was according to the standardized algorithm for the detection, confirmation, and subtype testing of PA according to the criteria of the 2008 Endocrine Society guidelines, 11 and all patients underwent computerized tomography and adrenal venous sampling to confirm IHA. 12 A lateralization index ≥2 was considered to indicate lateralization based on the results of adrenal venous sampling. The exclusion criteria were (a) other forms of secondary hypertension or APA, (b) an estimated glomerular filtration rate (based on the modification of diet in renal disease criteria) <45 ml/ min/1.73 m 2 , and/or serum creatinine >176 μmol/L, (c) hemorrhagic or ischemic stroke, and myocardial infarction within the previous 3 months, (d) percutaneous transluminal angiography received within the previous 3 months, and (e) allergy to iodinated contrast agent.…”
Section: Patient Populationmentioning
confidence: 99%